Monitoring the presence of genetically modified potato EH92-527-1 (BPS-25271-9) in commercial processed food - Maria Giovanna Tilocca; Gianfranca Serratrice; Maria Agostina Oggiano; Maria Rosalba Mancuso; Ilaria Mascia; Edoardo Marongiu; Bruna Vodret (Italian Journal of Food Safety, 2014)
The Amflora (EH92-527-1) potato is a genetically modified (GM) potato in which only starch of the amylopectin form is produced. This has been achieved by intervening with the biosynthesis of starch in this variety of potato. The Amflora potato is solely grown for the purposes of enhancing its industrial application. Although the Amflora potato is not fit for human consumption, the presence of the potato itself or any of its derived products in the food chain cannot be excluded, it should be considerate adventitious or technically unavoidable and can be accepted in a proportion no higher than 0.9%. To achieve the goal of our work we analysed forty-five potato-derived products to evaluate transgenic potato presence by real time polymerase chain reaction, obtaining negative results. In order to verify the correct application of the law and to assure the quality for the consumer, it is necessary to continue GM monitoring to verify the adventitious presence itself in food.